Harmonization of Customary Law and Environmental Regulations Study of Customary Rights in the Liku Keruga Tradition in Sabu Raijua Regency - Ernesta Arita Ari, Yoseph Djara Hae (Faculty of Law, Universitas Pekalongan, 2025)
The Liku Keruga tradition in Wadumaddi Village is part of customary law that has been passed down from generation to generation and plays a role in the management of marine resources, especially in the collection of coral reefs for the manufacture of whiting. This tradition is not just an economic activity, but also reflects the cultural identity of the local community. Indigenous communities apply strict rules regarding the time, amount, and parties allowed to take, so that resource utilization remains controlled and not excessive. However, national regulations prohibiting the exploitation of coral reefs raise the potential for conflict with long-established customary law. This research aims to analyze the existence of customary rights in the Liku Keruga tradition and its implications for the national legal system. Using juridical-normative and socio-legal approaches, this research explores the extent to which customary law can still play a role in the management of marine natural resources amid increasingly stringent environmental regulations. The results show that although customary law has a mechanism for sustainable management, its recognition in national regulations is still limited. Therefore, harmonization measures are needed through regional policies that can accommodate the practice of Liku Keruga without neglecting the protection of marine ecosystems.